تقييم فعالية تقنية فتح العضة في تدبير التهاب الأذن الوسطى المصلي المزمن عند الأطفال - نور الله عبد الوهاب; ابراهيم مصطفى; عثمان لمى (Latakia University Journal -Medical Sciences Series, 2016)
يعد التهاب الأذن الوسطى المصلي النمط الأكثر شيوعاً من التهابات الأذن الوسطى وخاصة عند صغار السن (2-5 سنوات). يعود السبب الأساسي إلى سوء تهوية الأذن الوسطى المؤدي لتجمع سائل غير قيحي فيها، حيث تلعب عدة عوامل دوراً هاماً في الإمراضية كسوء وظيفة نفير أوستاش , وضخامة الناميات , والأسباب التحسسية والاضطرابات المناعية والاستقلابية. إن العَرَض الرئيس له هو ضعف السمع , حيث يمكن يؤدي التهاب الأذن الوسطى المصلي غير المعالج إلى نقص سمع دائم. كما أن المعالجة التقليدية له ليست ناجحة في عدد لا بأس به من الحالات. هدفت هذه الدراسة إلى تقييم فعالية تقنية فتح العضة في تدبير التهاب الأذن الوسطى المصلي المزمن عند الأطفال، حيث أجريت هذه الدراسة السريرية في العيادات الأذنية في مشفى الأسد الجامعي في اللاذقية. شملت الدراسة عينة عشوائية مكونة من (30) حالة التهاب أذن وسطى مصلي مزمن. تراوحت أعمارهم بين 2 – 10 سنوات. قسمت العينة إلى مجموعتين: - مجموعة الدراسة: 15 طفلاً لديهم التهاب أذن وسطى مصلي مزمن وخضعوا لتقنية فتح العضة. - المجموعة الشاهدة: 15 طفلاً لديهم التهاب أذن وسطى مصلي مزمن وخضعوا للعلاج بالبروتوكول الدوائي المستخدم. تمت متابعة المرضى بعد شهر واحد، وثلاثة أشهر, وستة أشهر. حيث تم تقييمهم بالاعتماد على اختبار المعاوقة السمعية حيث أظهرت النتائج وجود فروق ذات دلالة إحصائية بين المجموعتين لصالح مجموعة التجربة، وذلك في الشهرين الثالث والسادس التاليين لتطبيق فتح العضة باستخدام الجهاز الإكريلي المتحرك، وللأعمار الأقل من 8 سنوات وفي حال عدم وجود ضخامة ناميات (P<0.05). Overview: Otitis media with effusion (OME) is the most common type of Otitis media (OM), especially in young children between 2-5 years. The main cause of this type is the decrease in ventilation of the middle ear, which creates purulent fluid. Several factors play a significant role in etiology as Eustachian tube dysfunction, adenoid hypertrophy and allergically causes, in addition to the immunological and metabolic disorders. The main symptom of (OME) is poor hearing, which may lead to permanent hearing loss if untreated. The traditional treatment of (OME) has not been successful in quite a number of cases. Aim of study: Evaluation of the effect of bite opening technique in management of chronic otitis media with effusion in children. Materials and Methods:This clinical study included 30 cases of otitis media with effusion. Ages of patients were between 2 - 10 years old, which were managed at the Auditory Clinics at Al-Assad University Hospital in Lattakia. The sample was divided into two groups: - Study Group: /15/ case of chronic otitis media with effusion. Bite opening was applied in these cases. - Control Group: /15/ case of chronic otitis media with effusion. These cases were managed by the medical protocol. The follow-up evaluation was conducted after one month, and in the third and sixth months, by using tympanometry test done by ENT specialist. Results: The study showed that bite opening technique has a significant effect in the third and sixth months following the application of the acrylic bite opening appliance, and in children free of adenoids, under the age of 8 years (P<0.05).